A STUDY OF TRANSFORMATIONAL LEADERSHIP OF SCHOOL ADMINISTRATORS BASED ON OPINIONS OF TEACHERS UNDER THE OFFICES OF SECONDARY EDUCATION SERVICE AREA IN NORTHEASTERN - Julsuwan, Suwat; Chinacarawat, Nawaratwadee (Journal of MCU Nakhondhat, 2020)
The purposes of this research were 1) to study current and desirable characteristics of transformational leadership of school administrators based on opinions of teachers Under the Offices of Secondary Education Service Area In Northeastern and 2) to compare transformational leadership of school administrators Under the Offices of Secondary Education Service Area In Northeastern, were classified by sex, age, work experience and education level. The sample of this research consisted of 384 the teacher used as a sampling group by using a multi-stage sampling. The statistics for analyses of data included the mean, standard deviation t – test and F – test. The results were as followed: 1) The study current and desirable characteristics of transformational leadership of school administrators based on opinions of teachers Under the Offices of Secondary Education Service Area In Northeastern as followed the current characteristics as a whole were medium level and the desirable characteristics as a whole were high level. 2) The compare transformational leadership of school administrators based on opinions of teachers Under the Offices of Secondary Education Service Area In Northeastern, were classified by the sex, the age, the work experience and the education level as followed the current characteristics and the desirable characteristics both sex, age, work experience and education level as a whole were different opinion on a statistic significant at the level .05